2009
DOI: 10.1369/jhc.2009.953547
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative In Situ Detection of Phosphoproteins in Fixed Tissues Using Quantum Dot Technology

Abstract: S U M M A R Y Detection and quantitation of phosphoproteins (PPs) in fixed tissues will become increasingly important as additional inhibitors of protein kinases enter clinical use and new disease entities are defined by molecular changes affecting PP levels. We characterize fixation conditions suitable for accurate PP quantitation that are achievable in a clinical laboratory and illustrate the utility of in situ quantitation of PPs by quantum dot (QD) nanocrystals in two models: (1) a therapeutic model demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 39 publications
(47 reference statements)
1
12
0
Order By: Relevance
“…Indeed, we observed that pSTAT5 in AML blasts with FLT3/ITD mutation as assessed by IHC in bone marrow biopsies is particularly strong compared to AML blasts with wild-type FLT3 [14] . We confirmed these qualitative data and using immunofluorescent assay showed a significantly higher nuclear expression of pSTAT5 in FLT3/ITD-positive cases compared to FLT3 wild-type cases [15] . In a similar line of thought, we studied another disease with constitutive tyrosine kinase activation, i.e.…”
Section: Applications Of Pp Detection In Diagnosis and Prognosis Assesupporting
confidence: 78%
See 2 more Smart Citations
“…Indeed, we observed that pSTAT5 in AML blasts with FLT3/ITD mutation as assessed by IHC in bone marrow biopsies is particularly strong compared to AML blasts with wild-type FLT3 [14] . We confirmed these qualitative data and using immunofluorescent assay showed a significantly higher nuclear expression of pSTAT5 in FLT3/ITD-positive cases compared to FLT3 wild-type cases [15] . In a similar line of thought, we studied another disease with constitutive tyrosine kinase activation, i.e.…”
Section: Applications Of Pp Detection In Diagnosis and Prognosis Assesupporting
confidence: 78%
“…Thus, fixed tissues must be used. Comparison of 5 commercially available fixatives showed that neutral buffered formalin fixation for durations typically used in clinical practice is satisfactory for quantitative assays [15] . Recently, a non-cross-linking (Streck; Omaha, Nebr., USA) tissue fixative was reported to significantly enhance the staining intensity of PPs compared with formalin [22] .…”
Section: Tissue Handlingmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection limit was as low as 10 colorectal cancer cells per ml (31). Apart from circulating tumor cell detection, Bodo et al (32) demonstrated that QD immunofluorescence had the possibility of in situ quantitation of phosphoproteins in fixed samples, providing a promising method for highly cell type-specific detection application in the future.…”
Section: Quantum Dots (Qds)mentioning
confidence: 99%
“…2b) a particular signal transduction protein may be useful to confirm the specificity and sensitivity. Such information is available for some phosphoproteins (12,15,16), but more published data are needed. Based on the same principles, validated antibody can be used for the truly quantitative analysis, using immunofluorescence assay (Fig.…”
Section: Automatedmentioning
confidence: 99%